Battle with Covid-19: the best recommendations for business professionals - Dinusha Dissanayake (Goodwood Publishing, 2021)
Purpose: Workforce healthiness is presently considering the cutting-edge duty in any organization today. The motive of this effort is to provide the best recommendations for business professionals for the survival of their business. Research methodology: The study was inductive and qualitative which conducted a methodical critique of literature as desk research. Pieces of writing in 2019 and 2020 have been reviewed. The content analysis is used as the analysis technique. Results: The researcher recognized workforce protection, business continuity, financial crisis management, contingency planning, and review as five themes associated with the core recommendations for business professionals throughout the corona rampant. Limitations: the secondary data and content analysis may cause subjective limitations to the study. Contribution: Throughout the study, business professionals can review core practices that can adapt in the enterprise under the Coronavirus. Thus, they can use research findings for strategy formulation in the future. Keywords: Covid-19, Recommendations, Business professionals